Upaya Peningkatan Kesadaran Masyarakat terhadap Bahaya dan Dampak Illegal Fishing melalui Program Pengabdian Kepada Masyarakat di Desa Rempanga, Kutai Kartanegara - Triyana, Lily; Murwani, Jeremia Lorenzo Stefano; Abidin, Zaenal; Afkarina, Afizah Nur; Indrastama, Mahogra; Heriyanto, Taufik; Kurahman, Fauzi; Iswadi, Al-Kirana Rizqiani; Affandi, Muhammad Bisri; Kasau, Muhammad Raja Mulia Darmawan; Tombuku, Aditia Ferdi (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
Illegal fishing poses a serious threat to aquatic ecosystems and community welfare. This research aims to increase awareness and understanding of the dangers and impacts of illegal fishing among the community of Rempanga Village, Loa Kulu District, Kutai Kartanegara Regency, East Kalimantan through a Community Service Program (PKM). The methods used include observation, questionnaire distribution, socialization, and environmental empowerment programs as follow-up actions. The results show that although the community is generally aware of illegal fishing practices, they experience difficulties in reporting such incidents. The socialization provided successfully increased participants' understanding of the dangers and impacts of illegal fishing practices, types of prohibited fishing gear (API), and reporting procedures. The Lestari Rempanga program, which involves tree seedling planting and fish seed distribution (restocking), successfully combined environmental conservation efforts with strengthening the community's spirit of mutual cooperation. In conclusion, this PKM activity made a positive contribution to raising community awareness and encouraging active participation in preserving river ecosystems, as well as supporting Rempanga Village's vision as a sustainable Minapolitan Village.